2011
DOI: 10.1101/gr.104018.109
|View full text |Cite
|
Sign up to set email alerts
|

High resolution mapping of Twist to DNA in Drosophila embryos: Efficient functional analysis and evolutionary conservation

Abstract: Cis-regulatory modules (CRMs) function by binding sequence specific transcription factors, but the relationship between in vivo physical binding and the regulatory capacity of factor-bound DNA elements remains uncertain. We investigate this relationship for the well-studied Twist factor in Drosophila melanogaster embryos by analyzing genome-wide factor occupancy and testing the functional significance of Twist occupied regions and motifs within regions. Twist ChIP-seq data efficiently identified previously stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 51 publications
5
80
0
Order By: Relevance
“…More recently, however, additional CRMs have been identified sharing similar spatiotemporal profiles to previously characterized CRMs, including one that shares close similarity with the sna expression pattern (Ozdemir et al, 2011;Perry et al, 2010). Another recent study presumably labeled this CRM as a 'shadow' enhancer because it is located at a distance from the snail gene, whereas the proximally located CRM was defined as the primary acting enhancer (Perry et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…More recently, however, additional CRMs have been identified sharing similar spatiotemporal profiles to previously characterized CRMs, including one that shares close similarity with the sna expression pattern (Ozdemir et al, 2011;Perry et al, 2010). Another recent study presumably labeled this CRM as a 'shadow' enhancer because it is located at a distance from the snail gene, whereas the proximally located CRM was defined as the primary acting enhancer (Perry et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…sna 1 /sna 18 ) to viability, whereas the other group was limited to assaying early gastrulation defects presumably because a large deficiency background was used; (2) our deletions were guided by our own Twist ChIP-seq data (Ozdemir et al, 2011), effectively guiding definition of the distal CRM as a larger region (~2.0 kb), (3) a spacer sequence (i.e. ampicillin resistance cassette) was not put in place of deletions in our constructs, which allowed us to assay whether native spacing is important; (4) the sna-coding sequence, which may possibly influence cis-regulatory mechanism or stability of transcripts, was left intact within our reporter constructs; and (5) the other group did not assay the gastrulation defects associated with the distal CRM delete large transgene but relied on cDNA rescue data conducted previously (Hemavathy et al, 2004).…”
Section: Rescue Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, Twist consensus sites differ substantially from canonical E-box sites (Ozdemir et al, 2011). We took an unbiased approach to identifying binding sites for Twist1 in the Sox9 locus and mined ChIP-seq (ChIP followed by sequencing) data from a human mammary epithelial cell line (Casas et al, 2011).…”
Section: -Catenin and The Twist Family Interact In Cranial Mesenchymmentioning
confidence: 99%
“…A target gene was assigned to DV enhancers only if the enhancer's expression domain overlapped and resembled the gene's expression domain (Supplemental Material). For this purpose, published mRNA in situ hybridization data from the Berkeley Drosophila Genome Project (BDGP) (Tomancak et al 2002(Tomancak et al , 2007Hammonds et al 2013) database were used for enhancers identified by Kvon et al (2012) and Ozdemir et al (2011). For some of these enhancers, no target gene was identified with confidence, and thus those enhancers were not included in mRNA-seq analysis shown in Supplemental Figure S1 (Supplemental Material).…”
Section: List Of Known DV Enhancersmentioning
confidence: 99%